Development of Analytical Methods to Quantify Perfluorooctane Sulfonate and Related Compounds in the Environment - Valeria de Lourdes Ochoa-Herrera; Jim A. Field; Reyes Sierra-Alvarez (ACI Avances en Ciencias e Ingenierías, 2011)
Analytical techniques based on 19F NMR spectroscopy and HPLC-suppressed conductivity detection were developed to detect and quantify aqueous perfluoroctane sulfonate (PFOS), perfluoroctanoic acid (PFOA), and perfluorobutane sulfonate (PFBS). Chromatographic separation of the perfluoroalkyl surfactants (PFAS) was performed using a C18 reversed-phase column and a mobile phase consisting of a mixture of boric acid and acetonitrile. The detection limit for PFOS by 19F NMR was 3.6 mg L-1. The detection limit for PFOS, PFOA and PFBS by HPLC-suppressed conductivity detection was 1 mg L-1. The detection limits were shown to improve considerably if samples were pre-concentrated by solid-phase extraction. The detection limits for PFOS of pre-concentrated samples were 3.6 mg L-1 and 10 ug L-1 by 19F NMR and HPLC-suppressed conductivity detection, respectively. Comparison of these two methodologies showed that HPLC-suppressed conductivity detection should be preferred for routine quantification of these contaminants due to its simplicity, time efficiency, and accuracy. Conversely, 19F NMR can be used to characterize changes in the chemical structure of fluorinated compounds due to its inherent advantage of high specificity and no matrix interferences. The feasibility of utilizing total organic carbon (TOC) and chemical oxygen demand (COD) analysis for the quantitative detection of PFOS in aqueous samples was also investigated. Although, the TOC analysis provided reliable quantification of PFAS in aqueous samples, the non-specificity is a drawback of the technique. The dichromate-based COD method was found unsuitable for the analysis of PFOS due to the incomplete oxidation of the highly stable perfluorinated compound under the conditions evaluated.